Congress of Neurological Surgeons Systematic Review and Evidence-Based Guidelines on the Role of Radiosurgery and Radiation Therapy in the Management of Patients With Vestibular Schwannomas. Issue 2 (20th December 2017) - Germano, Isabelle M; Sheehan, Jason; Parish, Johnathan; Atkins, Tyler; Asher, Anthony; Hadjipanayis, Constantinos G; Burri, Stuart H; Green, Sheryl; Olson, Jeffrey J
Abstract: RADIOSURGERY VS OBSERVATION: Question: What are the indications for stereotactic radiosurgery (SRS) treatment vs observation for patients with intracanalicular vestibular schwannomas without evidence of radiographic progression? Recommendation: Level 3: If tinnitus is not observed at presentation, it is recommended that intracanalicular vestibular schwannomas and small tumors (<2 cm) without tinnitus be observed as observation does not have a negative impact on tumor growth or hearing preservation compared to treatment. RADIOSURGERY TECHNOLOGY: Question: Is there a difference in outcome based on radiosurgery equipment used: Gamma Knife (Elekta, Stockholm, Sweden) vs linear accelerator-based radiosurgery vs proton beam? Recommendation: There are no studies that compare 2 or all 3 modalities. Thus, recommendations on outcome based on modality cannot be made. RADIOSURGERY TECHNIQUE: Question: Is there a difference in outcome based on the dose delivered? Recommendation: Level 3: As there is no difference in radiographic control using different doses, it is recommended that for single fraction SRS doses, <13 Gy be used to facilitate hearing preservation and minimize new onset or worsening of preexisting cranial nerve deficits. Question: Is there a difference in outcome based on the number of fractions? Recommendation: As there is no difference in radiographic control and clinical outcome using single or multiple fractions, no recommendations can be given. RADIOGRAPHIC FOLLOW-UP, RETREATMENT, AND TUMORIGENESIS AFTER RADIOSURGERY: Question: What is the best time sequence for follow-up images after SRS? Recommendation: Level 3: Follow-up imaging should be obtained at intervals after SRS based on clinical indications, a patient's personal circumstances, or institutional protocols. Long-term follow-up with serial magnetic resonance imagings to evaluate for recurrence is recommended. No recommendations can be given regarding the interval of these studies. Question: Is there a role for retreatment? Recommendation: Level 3: When there has been progression of tumor after SRS, SRS can be safely and effectively performed as a retreatment. Question: What is the risk of radiation-induced malignant transformation of vestibular schwannomas treated with SRS? Recommendation: Level 3: Patients should be informed that there is minimal risk of malignant transformation of vestibular schwannomas after SRS. NEUROFIBROMATOSIS TYPE 2: Question: What are the indications for SRS in patients with neurofibromatosis type 2? Recommendation: Level 3: Radiosurgery is a treatment option for patients with neurofibromatosis type 2 whose vestibular schwannomas are enlarging and/or causing hearing loss.  The full guideline can be found at: https://www.cns.org/guidelines/guidelines-management-patients-vestibular-schwannoma/chapter_7 .